Adolescent girls' knowledge about puberty and reproductive health: a test from primary schools in the City of Semarang - Chusnul Zulaika (Institute Of Computer Science (IOCS), 2023)
Teenagers have a very important role in the sustainability of the future of a nation. Teenagers are prospective individuals of the productive age population who in time will become actors in development so they must be prepared to become quality human resources. During adolescence, physical changes occur, including growing taller, increasing body weight, enlargement of the pelvic area, growth of breasts, changes in voice, appearance of hair in the pubic and armpit area, vaginal discharge, and menstruation. However, most young women do not realize that they are already fertile. The aim of this research was to determine the difference in knowledge of adolescent girls about puberty who had been given knowledge and those who had not been given knowledge about puberty at SDN Wonolopo 1 Mijen District. This research is a quantitative study with a quasi experimental research design, without using a control group with total sampling. This research was carried out involving 67 respondents. Data analysis using univariate analysis and bivariate analysis using paired sample t-test.In accordance with the results of the paired samples test, the significance value was 0.000. Because p < 0.05, it can be concluded that there isdifferences in adolescent girls' knowledge about puberty and reproductive health on reproductive health